Analisis Penanganan Kekerasan Seksual berbasis Online dalam Konstruksi Hukum di Indonesia - Helen Intania; Wahyu Satria WPW (LITERATUS, 2022)
During the pandemic, most of the community's activities were carried out at home by doing work from home and school from home . At the beginning of 2021 internet users in Indonesia reached 202.6 million people or 73.3% of the total population of Indonesia. The more massive communication via online does not rule out the greater the possibility of online gender-based violence (KBGO) in social media. In the last 3 years, cases of online-based sexual violence (KSBO), which is a form of KBGO, have continued to increase in Indonesia, including during the Covid period. From 2019 and 2020, Komnas Perempuan has recorded 455 cases of onlinebased violence against women reported through victim service agencies. The existence of the Law on Criminal Acts of Sexual Violence (UU TPKS) is important to protect sexual violence, including KSBO. The TPKS Law is expected to adequately regulate KSBO not only in its form but also in the protection of victims of KSBO. This research uses normative juridical research with a qualitative case approach. Based on the results of the research, there are 9 forms and patterns of online-based sexual violence, which consist of: 1) Undesirable production of sexualnuanced Electronic Material/Information; 2) Modification of sexually nuanced material/information; 3) Threats of Dissemination of Sexual Material/Information; 4) Dissemination of material/electronic information with sexual nuances; 5) Selling material/electronic information with sexual nuances; 6) Sexual Harassment; 7) Sexual Exploitation; 8) Sexual Bullying and 9) Sexual stalking. This KSBO mode varies; both the media used and the purpose/motivation of the actions taken. The complexity of handling KSBG cases is caused by layered and continuous barriers in assisting victims of online-based sexual violence